Cooperative learning: method of work in the classroom to facilitate the coexistence - Cano Tornero, María del Carmen (Avances en Supervisión Educativa, 2014)
The present communication is immersed in the investigations conducted on the application of the methods of Cooperative Learning in the classroom, through the Creativity and taking as resource the use from the TIC. It has as it bases the general Conclusions found and the produced Effects on the development of the activities, in the importance that has the social interaction for the coexistence in any educative scope. We set out an interaction between equal and, student and professor; coordinating interests, collective decision making, mutual aid, through dialogue, and always valuing and trusting the student. To conclude and to affirm, without doubt, that the processes of Interaction in the classroom improve the execution of the students in the cooperative activities.
Keywords: cooperative learning; TIC; creativity - interactive digital slate; innovating experience; scholastic coexistence